Vulnerability of rural workers to pesticides - Dias Xavier, Mariza; Tatielli Alves Urcino, Andréia; Mendes dos Santos, Gustavo; Ornelas Cunha, Franciele; Alves Paiva, Patrícia; Aparecida Marques Diamantino, Neiva; Donato Bauman, Claudiana; Veloso Dias, Orlene (Revista Unimontes Científica, 2020)
Abstract: Introduction: The excessive or inadequate use of pesticides can directly or indirectly interfere with human and environmental health, representing one of the major public health problems. Objective: To know the opinions of the rural workers about the health risks related to the use of pesticides. Methodology: This is a descriptive-exploratory research, with a qualitative approach. It was carried out with 13 rural workers in a rural district from a municipality located in the North of Minas Gerais, Brazil. The collected data were typed in Word and later analyzed using the ATLAS.ti 7 software, employing the Thematic Content Analysis. Results: The rural workers presented a low schooling level and a superficial knowledge about the health risks involved in the handling of any type of pesticides. Conclusion: The results revealed the social vulnerability of these rural workers when daily handling pesticides in their work activities, and the risks related to their health became evident. Resumo: Introdução: O uso abusivo ou indevido de agrotóxicos pode interferir de forma direta ou indireta às condições de saúde humana e do meio ambiente, constituindo um dos principais problemas de saúde pública. Objetivo: Conhecer as percepções dos trabalhadores rurais sobre os riscos relacionados ao uso de agrotóxicos para sua saúde. Metodologia: Trata-se de uma pesquisa do tipo descritivo-exploratória, com abordagem qualitativa. Foi realizada com 13 trabalhadores rurais em um distrito rural de um município do Norte de Minas Gerais, Brasil. Os dados foram transcritos no programa WORD, posteriormente foram analisados no programa ATLAS.ti 7 com base no referencial de Análise de Conteúdo Temática. Resultados: Os resultados revelam baixo nível de escolaridade dos trabalhadores e que esses possuem conhecimento superficial sobre os riscos à saúde que o manuseio de qualquer tipo de agrotóxicos pode trazer. Conclusão: Diante dos achados ficou evidente a vulnerabilidade social desses trabalhadores rurais no dia a dia ao manusear os agrotóxicos, bem como os riscos de danos à integridade da saúde dos mesmos.